Patient learning. (Economist, 2019)
The article discusses the operation of Lambda School, a company that provides training to potential employees. Co-founded by chief executive officer (CEO) Austen Allred, the company matches labor supply and demand by offering employee training. It offers several online courses that train candidates to develop software at technology firms. According to data, 85 percent of students who took the company's course finished it.